2017
DOI: 10.1159/000479403
|View full text |Cite|
|
Sign up to set email alerts
|

Thermal Preconditioning May Prevent Tendon Adhesion by Up-Regulating HSP72 in Rats

Abstract: Background/Aims: The study aims to determine the effects of thermal preconditioning on tendon adhesion by regulating the expression of heat shock protein 72 (HSP72) in rat models. Methods: Sixty male Wistar rats were collected and randomly assigned into the thermal preconditioning and control groups. During the 4th and 8th weeks following surgery, 15 rats were sacrificed in each period respectively, and their tendon adhesion was observed and evaluated. Biomechanical testing was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, as an anti-apoptotic chaperone and through its chaperone activity, HSP70 tightly regulates inflammatory responses via the nuclear factor-κβ signaling pathway, which is a critical pathway in mediating inflammatory responses (35). A previous study additionally demonstrated that TP reduced tendon adhesion via upregulating HSP72 expression (36). Furthermore, HSPs serve a substantial role in dealing with environmental stresses, including heat stress, whereas TP increases the mRNA levels of rhopalosiphum padi HSPs (37).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, as an anti-apoptotic chaperone and through its chaperone activity, HSP70 tightly regulates inflammatory responses via the nuclear factor-κβ signaling pathway, which is a critical pathway in mediating inflammatory responses (35). A previous study additionally demonstrated that TP reduced tendon adhesion via upregulating HSP72 expression (36). Furthermore, HSPs serve a substantial role in dealing with environmental stresses, including heat stress, whereas TP increases the mRNA levels of rhopalosiphum padi HSPs (37).…”
Section: Discussionmentioning
confidence: 87%
“…Although to a large degree, more precise approaches of imaging and radiotherapy aid in achieving the successful local control of NPC, however, distant metastases remained challenging for NPC treatment 3 . Various long non‐coding RNAs (lncRNAs) involve in regulating apoptosis of NPC 4 revealing lncRNAs as promising diagnostic markers and therapeutic targets of NPC.…”
Section: Introductionmentioning
confidence: 99%